Dye‐Sensitized Solar Cells Based on (Donor‐π‐Acceptor)2 Dyes With Dithiafulvalene as the Donor. Issue 7 (27th May 2014) - Lee, Ting‐Hui; Hsu, Chih‐Yu; Liao, You‐Ya; Chou, Hsien‐Hsin; Hughes, Heather; Lin, Jiann T.
Abstract Dipolar metal‐free sensitizers (D‐π‐A; D=donor, π=conjugated bridge, A=acceptor) consisting of a dithiafulvalene (DTF) unit as the electron donor, a benzene, thiophene, or fluorene moiety as the conjugated spacer, and 2‐cyanoacrylic acid as the electron acceptor have been synthesized. Dimeric congeners of these dyes, (D‐π‐A)2, were also synthesized through iodine‐induced dimerization of an appropriate DTF‐containing segment. Dye‐sensitized solar cells (DSSCs) with the new dyes as the sensitizers have cell efficiencies that range from 2.11 to 5.24 %. In addition to better light harvesting, more effective suppression of the dark current than the D‐π‐A dyes is possible with the (D‐π‐A)2 dyes.